Development of Number System; Hindu-Arabic and Devanagari - Shahi, Yubraj (Prajnik Bimarsha प्राज्ञिक विमर्श, 2023)
Number and symbols are the preliminary study of mathematics learning. This study focuses to investigate the good information about number system. Thus, the main objective of the study was to explore the number perception on human mind and analysis the historical development of Hind-Arabic and Devanagari number system. The research was conducted on the basis of content analysis approach from primary and secondary data. So, design of this research was qualitative research and Historical descriptive. The source of data for this study were taken from historical documents, archives, websites, research article, related journals, authorized books, consulting with research persons, libraries, department of archaeology etc. The researcher applied open-ended interview with recourse persons to make study strong and valid.What is the origin of number? How to perceive the number in primitive people? And how was the developing phase of the Hindu-Arabic, and Devanagari number system? Be the main problem of this study. The data analysis and interpretation procedure was guided from triangulation process as well as explain analytically, logically, and cross matching comparatively. At last study concluded, the number is the result of social phenomena. The concept of number and symbols is comes from ancient human culture and human civilization. So, the number is invention from different human civilization but is not from mathematicians. All animal and men have the number sense. Ancient people used concrete objects for notation before the recorded history. Primitive people makes number concept from the define collection of objects. For Eg. “sun” and “moon” for 1, “eyes” and “breast” for 2 and so on. The modern decimal place-value counting was developed from ancient people’s one-to-one corresponding counting techniques. The foundation of Devanagari script is ancient Hindu (Nagari) script which was a branch of Brahmi script. Consequently, Hindu-Arabic number is revised form of ancient Hindu (Nagari) number. Moreover, the historical development of number is a way of motivating the learner and see the significance of its further study.